UNRAVELING CARBON IMPACT: ASSESSING EXPORT, COMPETITIVENESS, GDP, AND POPULATION IN INDONESIA'S OIL PALM TRADE - Erwinsyah Erwinsyah (EKUITAS (Jurnal Ekonomi dan Keuangan), 2024)
In Indonesia's oil palm commerce, this study investigates at the relationship between population growth, economic growth, market competitiveness, and export trade with carbon emissions. Time-series data from 1995 to 2021 collected from statistical sources is used in this study. This link is computed and analyzed using the econometric method. Lower carbon emissions in oil palm exports are correlated with sustainable practices and market competitiveness. To disentangle trade growth from environmental effect, sustainable land-use practices, deforestation reduction, and transparent supply chains are crucial. Given the erratic correlation between GDP and carbon emissions, striking a balance between economic expansion and environmental protection is imperative. Population expansion drives efforts to lower carbon footprints by influencing environmental awareness and the market for oil palm. Well-given initiatives such as clean technology, certification support, and sustainable trade policies have policy repercussions. Policymakers, industry players, and environmental groups working together can guarantee Indonesia's oil palm exports' long-term sustainability and ecological viability.